Alternative transarterial access for CoreValve transcatheter aortic bioprosthesis implantation. (May 2015) - Bruschi, Giuseppe; De Marco, Federico; Modine, Thomas; Botta, Luca; Colombo, Paola; Mauri, Silvia; Cannata, Aldo; Fratto, Pasquale; Klugmann, Silvio
<x xml:space="preserve">Abstract</x> Transcatheter aortic valve implantation (TAVI) is used to treat elderly patients with severe aortic stenosis who are considered extremely high-risk surgical candidates. The safety and effectiveness of TAVI have been demonstrated in numerous studies. The self-expanding CoreValve bioprosthesis (Medtronic Inc., Minneapolis, MN, USA) was the first transcatheter aortic valve to be granted the Conformité Européene (CE) mark in May 2007 for retrograde transfemoral implantation. However, TAVI patients are also often affected by severe iliofemoral arteriopathy. In these patients, the retrograde transfemoral approach carries a high risk of vascular injury, making this approach unusable. Alternative arterial access sites, such as the subclavian artery, the ascending aorta, and the carotid artery, have been used for retrograde implantation of the CoreValve bioprosthesis. In the present report, we present the procedural considerations, risks, and benefits of the different types of arterial access used to implant the CoreValve bioprosthesis.